2012
DOI: 10.1097/igc.0b013e3182473292
|View full text |Cite
|
Sign up to set email alerts
|

Different Levels of Sialyl-Tn Antigen Expressed on MUC16 in Patients With Endometriosis and Ovarian Cancer

Abstract: Estimation of the sTn/MUC16 level may be useful for discriminating endometriosis from ovarian cancer and for evaluating the clinical stage, cytological grade, and histological type of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…STn antigen expression is observed in many epithelial cancers, and its expression correlates with enhanced expression of ST6GalNAc-I [108] and elevated serum levels of STn antigen are associated with poor prognosis [109,110]. Recent studies have shown that for patients with ovarian cancer, evaluating the serum levels of STn in circulating mucins, such as MUC16 (now known to be the CA125 antigen), a mucin produced by ovarian tumors and whose ectodomain is found in blood, may aid in diagnosis, tumor staging, and type [111]. STn expression is also enhanced in patients with ovarian cancer, but not in patients with en-dometriosis, in contrast to expression of the antigen CA125, which is often overexpressed in both conditions [111].…”
Section: Expression Of Tn Antigen In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…STn antigen expression is observed in many epithelial cancers, and its expression correlates with enhanced expression of ST6GalNAc-I [108] and elevated serum levels of STn antigen are associated with poor prognosis [109,110]. Recent studies have shown that for patients with ovarian cancer, evaluating the serum levels of STn in circulating mucins, such as MUC16 (now known to be the CA125 antigen), a mucin produced by ovarian tumors and whose ectodomain is found in blood, may aid in diagnosis, tumor staging, and type [111]. STn expression is also enhanced in patients with ovarian cancer, but not in patients with en-dometriosis, in contrast to expression of the antigen CA125, which is often overexpressed in both conditions [111].…”
Section: Expression Of Tn Antigen In Tumorsmentioning
confidence: 99%
“…Recent studies have shown that for patients with ovarian cancer, evaluating the serum levels of STn in circulating mucins, such as MUC16 (now known to be the CA125 antigen), a mucin produced by ovarian tumors and whose ectodomain is found in blood, may aid in diagnosis, tumor staging, and type [111]. STn expression is also enhanced in patients with ovarian cancer, but not in patients with en-dometriosis, in contrast to expression of the antigen CA125, which is often overexpressed in both conditions [111]. Expression of STn antigen is associated with poor prognosis, and in the case of gastrointestinal adenocarcinomas its expression is dependent on the aberrant expression of ST6GalNAc-I [112].…”
Section: Expression Of Tn Antigen In Tumorsmentioning
confidence: 99%
“…Although the association between ST6GalNAc-I and the expression of sTn is still not fully clear, sTn antigen is highly expressed in most gastric [22], colorectal [23], ovarian [24], breast [25] and pancreatic carcinomas [26] whereas no expression is observed in the respective normal tissues. The positive correlation of sTn with carcinoma aggressiveness and poor prognosis has motivated the research on sialyl-Tn role in cancer cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…4 It was recently found that the glycosylation of CA125 in patients with EOC is different from that in healthy subjects and patients with benign ovarian neoplasms, providing an attractive target for qualitative evaluation of this mucin. [5][6][7] However, the biochemical tools for specifically detecting such altered glycosylation are limited.…”
mentioning
confidence: 99%